El invento bizantino de las minúsculas griegas frente a las unciales helenas tradicionales - Santana Henríquez, Germán (Cuadernos del CEMYR, 2016)
The invention of the Greek Byzantine minuscule against traditional Hellenic uncials».A fact that is often overlooked in the history of mankind is the invention of lowercase Greek letter in the ninth century AD during the Byzantine Empire. Until then, Greek texts were written in uncial or capital. Byzantine copyists turn all those works Greek antiquity had bequeathed to the West into this new point. Those texts which were not rendered into the new letter ended up being forgotten and irretrievably disappearing.Thus, both the records and the memory of a near or remote past depended highly on this new way of writing which became fashionable during the Middle Ages and found its way into the present day.